Role of Kudumbashree micro financing in the women empowerment with special reference to the Malappuram District of Kerala - P. Shamshadali; C.K. Anjena and K. Faris Mohammed (Indian Journal of Economics and Development, 2019)
Background/Objectives: Women empowerment is the process through women attaining the ultimate independency of their lives and acquires the ability to take decisions on their taste and preferences. State Poverty Eradication Mission of Kerala State Government launched Kudumbashree women empowerment through poverty eradication program in 1998 and setup in Malappuram District. Kudumbashree contributes its valuable positive impacts on both the Social and Economic aspects of the Country. The study is aimed to find out the role and status of Kudumbashree units of Malappuram District of Kerala in the woman empowerment. Methods/Statistical analysis: The study has done on the Primary data which collected from the Ninety Five Community Development Society (CDS) members of Kudumbashree through structured questionnaire. Personal and telephonic interview methods of data collection have been opted. Likert five point scales and its average are considered for the analysis on collected data. Findings: After the analysis the study has found that, Malappuram District where the majorities are living in rural areas the units of Kudumbashree play a vital role to bring the women in the main stream of the society. The status of Kudumbashree operations is satisfactory and the different training programs are getting right results. Application: The District where the Kudumbashree women empowerment program launched initially demands much better plans and liberalizations to enhance the members of units across the district for the better positive impacts on both social and economic aspects of the society.